ELECTRICITY INVESTMENT AND INTERNATIONAL GOVERNANCE: A CASE STUDY FROM INDONESIA – CHINA ELECTRICITY COOPERATION IN EAST KALIMANTAN, BERAU - i nyoman aji suadhana rai; raden maisa yudhono (Jurnal Ilmiah Dinamika Sosial, 2017)
ABSTRACTAll of the government always try boost the economy sector by accommodate the investment in their country. In Indonesia the cooperation sometimes started by the private parties. However, most of the private sector were based not on the principle of liability or ability in accordance with what is promised by them. The projects run by the Indonesian government should receive special attention, especially electricity projects, where Indonesia is predicted to deficit electricity in 2019. China is one of Indonesia's strategic partners in maximizing the potential of the region through infrastructure development. Especially for power projects with China holding considerable attention for the government of Indonesia, Based on the above statement, this study focused on electricity investment projects with the Chinese and Indonesia side to creating governance for the region and globally. This study needed to know because to understand the prospect of implementation the scheme of Public Private Partnership on both country. The result of this study found that the scheme of Private Public Partnership located in East Kalimantan would give a stabilized in both of the economic and politic steam in the region. However, this scheme is also could take risk in the national compensation benefit in the far future.Keywords: China, Indonesia, Infrastructure, Electricity, Public Private Partnership